A Critical Review of Symptom Management of Auditory Hallucinations in Patient with Schizophrenia - Suryani (Universitas Padjadjaran, 2017)
Auditory hallucinations are a key symptom of schizophrenia. It is estimated that the prevalence of auditory hallucinations in people with schizophrenia range from 64.3% to 83.4%. The auditory hallucinations impacted on daily lives of the sufferer. An extensive review of the literature was undertaken to find symptom management that has been developed in reducing auditory hallucinations from CINAHL, PsyInfo, Health and Medical Complete, ProQuest Psychology Journals, ProQuest Social Journals, Science Direct, Web of Science and Scopus. Based on the analysis of the 15 articles, evidence was suggested that CBT and other psychological treatments have beneficial for individuals who experience auditory hallucinations. However, individuals who experience auditory hallucinations are not just sufferers who need to be treated but people who can develop their own strategies of living with auditory hallucinations. Therefore it is important for nurses to involve them in the management of the auditory hallucinations.